Pengaruh Penggunaan Senyawa Pengomplek dan Bahan Tambahan Terhadap Mutu Tinta Pemilu dari Ekstrak Gambir (Uncaria gambir Roxb) - Muchtar, Hendri; Anova, Inda Three; Ardinal, Ardinal (Institution for Industrial Research and Standardization of Industry - Padang, 2014)
Election ink is applied to the forefinger of voters during election in order to prevent electoral frauds such as double voting. The current election inks contain silver nitrate solutions to make it more durable which stains the skin on exposure to ultraviolet light, leaving a mark that is impossible to wash off and is only removed as external skin cells are replaced. But the silver nitrate solution may damage the human skins and is poisonous to the environment. This research was carried out to investigate the use of gambir extracts for election inks as environment-friendly raw materials. The aim of this study was to obtain the optimal ink from gambir extrac which technically could meet quality requirements of the election ink. In this study, gambir was extracted through the following refinement process; heating in boiling water, stirring, cooling, filtering, molding, and drying. The cube black then was dissolved in technical ethanol, added one of the complexing compounds FeSO4 and FeNO3 depending on the formula used. The best ink composition was 70% gambier extract in ethanol, 22% of FeSO4 saturated solution in ethanol, 5% of turmeric extract, and 3% of crystal violet solution 4%. This ink was more homogenous with violet color at pH 3.86 which gave rub resistant to water and soap. The ink stains could stay on finger skin for 3 days. Analytical results showed that the ink did not contain Pb, Cd, and Hg while Cu 65.04 ppm and fulfill the requirement of general election commitee number 16/2013.ABSTRAK Tinta pemiluÂ digunakan untuk identifikasi pada jari tangan pada waktu pemilihan umum atau kegiatan sejenis lainnya guna mencegah terjadinya kecurangan. Pada tinta pemilu saat ini digunakan bahan perak nitrat agar lebih tahan lama, namun penggunaan perak nitrat dapat merusak kulit dan bersifat racun. Untuk itu telah dilakukan penelitian pengaruh jenis bahan senyawa pengomplek dan bahan tambahan terhadap mutu tinta pemilu dari ekstrak gambir. Penelitian ini bertujuan untuk mendapatkan tinta dari ekstrak gambir yang secara teknis dapat memenuhi persyaratan kualitas tinta pemilu. Dalam penelitian ini gambir diolah menjadi cube black gambir melalui proses penghalusan, pemanasan dalam air mendidih, pengadukan, pendinginan, penyaringan, pencetakan, dan pengeringan. Selanjutnya cube black gambir dilarutkan dalam etanol teknis, ditambahkan salah satu dari senyawa pengomplek, FeSO4 dan FeNO3 tergantung formula yang digunakan. Komposisi tinta terbaik adalah 70 bagian ekstrak gambir dalam etanol, 22 bagian larutan jenuh FeSO4 dalam etanol, 5 bagian ektrak kunyit serta 3 bagian larutan kristal violet 4%. Tinta lebih homogen dengan warna yang dihasilkan violet, pH 3,86, tahan gosok terhadap air danÂ sabun. Daya tahan tinta dapat tahan sampai tiga hari, kandungan logam Pb, Cd, Hg tidak terdeteksi dan kandungan Cu sebesar 65,04 ppm, tinta memenuhi persyaratan Peraturan Komisi Pemilihan Umum nomor 16 tahun 2013.Â